RECONSTRUCTING EXHIBITIONS IN ART INSTITUTIONS. - Adamou, Natasha, editor; Giebelhausen, Michaela ([Place of publication not identified] : ROUTLEDGE, 2023)
Reconstructing Exhibitions in Art Institutions spans exhibition histories as anti-apartheid activism within South African community arts; collectivities and trade unions in Argentina; Civil Rights movements and Black communities in Baltimore; institutional self-critique within the neoliberal museum; reframing feminisms in USA; and revisiting Cold War Modernisms in Eastern Europe among other themes. An interdisciplinary project with a global reach, this edited volume considers the theme of exhibitions as political resistance as well as cultural critique from global perspectives including South Africa, Latin America, Eastern Europe, USA and West Europe. The book includes contributions by ten authors from the fields of art history, social sciences, anthropology, museum studies, provenance research, curating and exhibition histories. The edited volume finally examines exhibition reconstructions both as a symptom of advanced capitalism, geopolitical dynamics and social uprisings, and as a critique of imperial and capitalist violence. Art historical areas covered in the book include conceptualism, minimalism, modern painting, global modernisms, archives and community arts. This volume will be of interest to a wide range of audiences including art historians, curators, gallery studies and museum professionals, and also to scholars and students from the fields of anthropology, ethnography, sociology, and history. It would also appeal to a general public with an interest in modern and contemporary art exhibitions.
Keywords: Art -- Exhibitions -- Political aspects; Art -- Exhibitions -- Social aspects; Art museums -- Curatorship -- Political aspects; Art museums -- Curatorship -- Social aspects; Art and society -- History; HISTORY / General